Environment as a Moderating Variable in the Influence of Mental Health on Employee Performance - Titin, Titin; Yustiyawan, Rachman Halim; Alhakim, Bambang Amir; Riyanti, Apriani; Soesanto, Dasa Rahardjo (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
In the era of digital transformation and fluctuating market dynamics, employee psychological well-being has become a key determinant of organizational success. This study aims to analyze the influence of mental health on employee performance by positioning the work environment as a moderating variable. Using a quantitative approach, this study processed primary data from 200 respondents in industrial sectors with high work pressure. The analytical tool used was E-Views through the Moderated Regression Analysis (MRA) method to test the interaction effect between the independent and moderator variables. The results of the analysis indicate that mental health contributes positively and significantly to employee performance. Furthermore, it was found that the work environment functions as a moderating variable that strengthens the relationship (strengthening effect). These findings confirm that a conducive work environment, both physically and psychosocially, can mitigate the negative impact of employee mental degradation on their work output. The implications of this study suggest that organizational management should integrate mental health policies into the work environment design to achieve sustainable productivity.